Influence of student's perception on teachers' behavior on self-esteem and self-efficacy in between class ability grouping - Prihadi Kususanto, 1974-; Azlina Mohd. Kosnin, supervisor; Fakulti Pendidikan (2009)
Thesis (Sarjana Pendidikan (Psikologi Pendidikan)) - Universiti Teknologi Malaysia, 2009